Pengaruh perendaman ekstrak biji alpukat (persea americana) terhadap kekuatan transversal resin akrilik heat cured - Maria Jesicasari Tena; Nova Adrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: One of the mechanical properties of acrylic resin that must be considered in the selection of denture base materials is transverse strength. Transverse strength is needed to resist loads, pressure, and thrust while the mouth is working. Avocado seed extract (Persea americana) is a natural ingredient that can be an alternative to cleaning dentures. Objective: To determine the effect of immersing avocado seed extract (Persea americana) on the transverse strength of heat cured acrylic resin. Methods: This research applies a laboratory experimental study with a post test only group design. The research sample used 32 samples with a size of 65 mm x 10 mm x 2.5 mm, which were divided into 2 immersion groups, 100% avocado seed extract and aquades for 3 days 19 hours 25 minutes. Transverse strength measurement using Universal Testing Machine three point bending. Results: The average value of the transverse strength of heat cured acrylic after soaking in 100% avocado seed extract was 73.76 MPa and 86.03 MPa in aquades. Data were analyzed using the Shapiro-Wilk normality test and independent T test. Conclusion: The transverse strength of heat cured acrylic resin soaked in 100% avocado seed extract is lower than soaked in aquades.